2021
DOI: 10.1177/0308022621995112
|View full text |Cite
|
Sign up to set email alerts
|

Occupational balance and quality of life in mothers of children with cerebral palsy

Abstract: Introduction Occupational balance (OB) is an important concept in occupational therapy and is considered as an essential component of health and well-being. The aim of this study was to show differences in OB and quality of life (QoL) between mothers of children with cerebral palsy (CP) and typically developing children. Methods Thirty-six mothers of children with CP and 36 mothers of typically developing children participated in the study. The mothers’ OB was evaluated using the Turkish Occupational Balance Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…Two studies on occupational balance were based on the use of qualitative research methods ( 22 , 64 ). Studies that reported the use of measures of occupational balance in parents included parents of children aged 8 years or younger ( 36 , 37 ), or did not declare children's age ( 65 ). It is unclear whether parents of newborns or children under the age of 1 year were included since this was not described explicitly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies on occupational balance were based on the use of qualitative research methods ( 22 , 64 ). Studies that reported the use of measures of occupational balance in parents included parents of children aged 8 years or younger ( 36 , 37 ), or did not declare children's age ( 65 ). It is unclear whether parents of newborns or children under the age of 1 year were included since this was not described explicitly.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational balance of caregivers has shown to potentially influence both, their own health and the health of the person they cared for (22,35). There is increasing evidence, that occupational balance is clinically relevant in pediatrics, especially when it comes to parents of children with complex caring needs or critical health (22,23,(36)(37)(38)(39). Furthermore, a previous study indicated that there might be a link between mothers' occupations and their children's health as well (40).…”
Section: Introductionmentioning
confidence: 99%
“…Uhrmann et al (2019) developed a Norwegian version of OBQ11 and reported that it was feasible and had good face validity. Günal et al (2020) translated OBQ11 to Turkish and demonstrated its reliability and validity in a sample of 58 Turkish participants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Occupational Balance Questionnaire (OBQ) and the revised OBQ11 have been widely used by researchers to measure OB ever since its development (Borgh et al, 2018;Gunal et al, 2021;Håkansson et al, 2019aHåkansson et al, , 2019bHåkansson and Lexén, 2021;Kassberg et al, 2021;Magnusson et al, 2020;Wagman et al, 2016). The instrument, originally developed in Swedish, has been translated to a number of other languages (Gomez, 2017;Günal et al, 2020;Uhrmann et al, 2019;Yu et al, 2019), but not as yet to the Arabic language. The aim of the present study was thus to describe the translation process of the OBQ11 to Arabic and to evaluate its content validity, internal consistency, construct validity, and convergent validity.…”
Section: Introductionmentioning
confidence: 99%
“…Deviations in the engagement of meaningful activities cause changes of occupational balance, defined as a satisfying amount and variety of meaningful activities [ 32 ]. There is evidence that informal caregiving leads to limited occupational balance [ 29 , 31 , 33 ] and a need for interventions to support informal caregivers’ occupational balance [ 33 , 34 ]. Furthermore, occupational balance was found to be associated with health, quality of life and well-being [ 32 , 35 38 ].…”
Section: Introductionmentioning
confidence: 99%